LANDSLIDE FORENSIC AND PREDICTION USING DENDROGEOMORPHOLOGY - Iwan Gunawan Tejakusuma (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Landslide forensic can be investigated using dendrogeomorophological method. This method can be used to predict future landslide on the basis of the analysis of the past landslide. However, this method has not been used in Indonesia although the prospects of research using this method is possible. Plants will respond to a landslide event where plants in landslide area can be injured, tilted, scratched, the roots are damaged or partially removed. This plant can then continue to grow and track a record of the landslide event indicated by the abrupt changes in tree rings series. The combined study between the landslide geomorphology and plant response through the pattern changes in tree rings series can reveal landslide events so that the forensics of landslide can be described. Furthhermore the landslide events can be predicted both in time space, allowing for a more precise landslide disaster mitigation, spatial planning and management.